Aqua{N,N-dimethyl-N '- 1-(2-pyridyl)ethylidene ethane-1,2-diamine-kappa 3 N,N ',N ''}bis(thiocyanato-kappa N)nickel(II) - Gwaram, N.S.; Ali, Hapipah Mohd; Khaledi, H.; Saharin, S.M. (International Union of Crystallography, 2011)
In the title compound, [Ni(NCS)(2)(C11H17N3)(H2O)], the NiII ion is six-coordinated by the N,N',N"-tridentate Schiff base N atoms, two cis-positioned N-bound isothiocyanate groups and one water molecule. In the crystal, O-H...S hydrogen bonds link adjacent molecules into infinite layers parallel to the ac plane. The layers are further connected into a three-dimensional network via C-H...pi interactions. The -CH2-N(CH3)(2) fragment is disordered over two sets of sites in a 0.556 (5):0.444 (5) ratio.